AUDIT ON MEDICAL THORACOSCOPY IN PATIENTS WITH EXUDATIVE PLEURAL EFFUSION IN TERTIARY CARE HOSPITAL IN CENTRAL SRI LANKA - Nawarathne, Ishelda; Madegedara, Dushantha (International Journal of Research -GRANTHAALAYAH, 2025)
Introduction Pleural effusion is a common condition in respiratory medicine, yet about 20% of cases remain unexplained even after thorough evaluation, including closed pleural biopsy. Medical thoracoscopy (MT) has emerged as the preferred diagnostic and therapeutic tool for exudative pleural effusions, especially valuable for patients at high risk for more invasive procedures like VATS. At the National Hospital -Kandy in Sri Lanka, several deficits were identified in the thoracoscopy procedure, prompting a prospective audit aimed at improving service quality and patient care. British Thoracic Society guideline on thoracoscopy procedure was used as the standard for comparison with our data. Method This prospective, standard-based audit was conducted among 75 patients who underwent medical thoracoscopy at Respiratory Unit 11, National Hospital Kandy, Sri Lanka, between January 2021 and December 2022. Data collection was primarily carried out through direct questioning of patients, supplemented by information extracted from patient records and observations documented in a data collection form. This study evaluates key aspects of patient care following chest tube insertion, focusing on consent acquisition, real-time ultrasound use, and monitoring for complications like fever, pain, pneumothorax, and infection. It also examines post-procedure mobility, patient satisfaction, chest tube drainage duration, and hospital stay length to assess their impact on patient outcomes and improve chest tube management practices. Results Informed written consent was obtained from over 94% of patients. Pre-procedure chest CT was performed for 50% of patients, while only 60% had real-time ultrasound guidance during the procedure. No significant complications related to the thoracoscopy were reported. Most patients expressed satisfaction with the procedure, and 95% received a definitive diagnosis, with only 5% having an uncertain diagnosis. Discussion Significant deficiencies in the practice of medical thoracoscopy (MT) at National Hospital Kandy, Sri Lanka, have been identified. In response, we implemented several improvements: standard documentation templates were introduced to enhance record-keeping, real-time ultrasound scans were integrated to improve procedural accuracy, and a protocol for the safe and efficient transportation of samples was established. Additionally, we introduced small-gauge chest drains to minimize patient discomfort and enhance post-procedure pain management. These recommendations aim to systematically advance thoracoscopy practices, ensuring better patient outcomes and upholding high standards of care.